Social Crisis, Terrorism and Food Poverty Dynamics: Evidence from Northern Nigeria - Adebayo, Ogunniyi; Olagunju, Kehinde; Kabir, Salman K.; Adeyemi, Ogundipe (International Journal of Economics and Financial Issues, 2016)
Food security has become an issue of global concern in the recent time. Nigeria, with her huge endowed natural and human resources is not spared. However, food poverty in Northern Nigeria has come under threats since the emergence of series of attacks by a terrorist sect called ‘Boko Haram’ (BH). Since the emergence of the BH activities in Nigeria, sectors with direct impact on the wellbeing of the people has been negatively affected. The aim of this paper is therefore to examine the various ways in which the activities of BH have threatened food security and worsens food poverty in Northern zones (North West, North Central and North East) of Nigeria where the sects are dominating and imposing demeaning menace using 2010 Nigerian Living Standard Survey (NLSS) data. The data is analyzed using descriptive statistics and ordered probit. The study used mean food per capita expenditure to generate the poverty line and ordered the households into three categories; food poor, moderately food poor and food non poor. The estimate revealed that the mean food per capita expenditure (annually) was â‚¦25524.36 (128.23). The study further established that 84.85% of the households in northern Nigeria are food poor in which majority are rural households, male headed households and uneducated households. Furthermore, the study found that the activities of the sect have negatively impacted the wellbeing of the northern Nigerians and increases food poverty extremely. However, interventions such as donations from foreign organizations such as UNICEF, WHO, World Bank etc. were found to improve the food security and reduce food poverty of the northerners. Therefore, this study recommends increasing intervention effort by the Nigerian government and the international community in curbing the menace of “Boko Haram”. Also, state government and other stakeholders including non-governmental organization should boost awareness on productive opportunities for the unemployed women and youths; and establishment of training/development centers for the uneducated. Keywords: Terrorism, Food Poverty Dynamics, Northern Nigeria JEL Classifications: I32 P36 Q18